Bending the Bow : An Anthology of African Love Poetry - Chipasula, Frank Mkalawile (Book collections on Project MUSE., 2009)
From the ancient Egyptian inventors of the love lyric to contemporary poets, Bending the Bow: An Anthology of African Love Poetry gathers together both written and sung love poetry from Africa. This anthology is a work of literary archaeology that lays bare a genre of African poetry that has been overshadowed by political poetry. Frank Chipasula has assembled a historically and geographically comprehensive wealth of African love poetry that spans more than three thousand years. By collecting a continent's celebrations and explorations of the nature of love.